Experimental and Modelling Investigation of Re-Adhesion Mechanism of Detached Nanoparticles to Wafer Surface in Spin Rinse Process. (2nd July 2020) - Handa, N.; Hiyama, H.; Amagai, K.; Yano, A.
Abstract : Adhesive particles on polished wafers are detached by e.g. scrubbing, and removed by liquid flow from the wafer. However, the relationship between the characteristic of liquid flow and the removal of detached particles has not yet been examined in detail. Therefore, the re-adhesion of detached particles to wafer surfaces in liquid flow on rotating wafers was experimentally investigated. The number of residue particles on a wafer was counted using a defect inspection tool after de-ionized water (DIW) rinse for particle removal. To discuss the mechanism of particle removal, a model was constructed and compared with experimental results. The model is based on boundary layer theory of fluid dynamics and advection diffusion theory of transport phenomena for particle removal in liquid flow near the wafer surface. The model results confirmed that detached particles in liquid flow moved into the sublayer and re-adhered to the wafer surface by diffusion. Moreover, particles in the sublayer, where the liquid velocity is several hundred um/s, could not be moved from the sublayer and removed from the wafer. It was also found that the number of particles re-adhering to the wafer surface depends on the Sherwood number.